Association between cardiovascular health and human papillomavirus infection: analysis from NHANES 2005–2016 - Meng Li; Meiying Song (Frontiers in Public Health, 2024)
BackgroundGiven the strong association between cardiovascular disease and human papillomavirus (HPV) infection, this study aimed to assess the correlation between HPV infection and cardiovascular health (CVH) as represented by the Life’s Essential 8 (LE8) score.MethodsThis study employed analysis of data obtained from the National Health and Nutrition Examination Survey covering the period from 2005 to 2016. To examine the correlation between the CVH score and both HPV and high-risk HPV (HR-HPV) infections, this research utilized a combination of multivariable regression analysis, smooth curve fitting, and subgroup analysis, following adjustment for pertinent covariates.ResultsThis study included a total of 8,264 women, with an average age of 39.53 ± 11.24 years. The HPV prevalence was 43.43% overall, while the HR-HPV prevalence was 17.36%. In the fully adjusted model, an augmentation of 10 points in the CVH score correlated with an 8% reduction in the HPV infection rate [0.92 (0.88–0.96)], and a similar 8% decrease in the HR-HPV infection rate [0.92 (0.87–0.97)].ConclusionOur findings indicate that elevated CVH, as denoted by higher LE8 scores, correlates with a decreased of HPV infection rate among U.S. females. The LE8 score shows potential as a shared predictive biomarker for both CVH and HPV infection.